An ark on the Nile: the beginning of the Book of Exodus - Bodner, Keith (Oxford University Press, 2016)
"An Ark on the Nile: The Beginning of the Book of Exodus is a close-reading of Exodus 1-2 that analyzes the story as a reasonably self-contained unit, but suggesting that major plot movements in the book of Exodus are foreshadowed and anticipated here. Applying a number of insights from literary theory, Keith Bodner offers an illustration of further integration of biblical studies with cross-disciplinary narrative interpretation